Potential Predictors and Survival Analysis of the Relapse of HIV-Associated Cryptococcal Meningitis: A Retrospective Study - Li, Yao; Lu, Yanqiu; Nie, Jingmin; Liu, Min; Yuan, Jing; Li, Yan; Li, Huan; Chen, Yaokai (Frontiers in Medicine, 2021)
Objective: We intend to investigate the relapse of HIV-associated cryptococcal meningitis (CM), assess potential predictors and conduct survival analysis, with a view to establishing a valid reference for the management of the relapse of CM. Method: This is a retrospective study in Chinese patients with HIV-associated CM and those who experience relapse of CM. Baseline demographic, laboratory and clinical characteristics of patients with HIV-associated CM were collected. Predictors for relapse of HIV-associated CM were analyzed using univariate and multivariate logistic regression. Survival probability in relapse cases was determined by Kaplan-Meier survival curves. Results: During the study period, 87 of 348 (25.0%) HIV patients experienced the relapse of CM. CD4+ T-cell counts, antiretroviral therapy (ART) status and the time from symptom onset to presentation were all statistically associated with the relapse of CM (p = 0.013, 0.018 and 0.042, respectively). The overall survival among 46 HIV CM relapse patients whose survival information were obtained, was 78.3%. The proportion of patients who died after antifungal treatment for CM was greater in those whose interval from symptom onset to presentation ≥4 weeks, compared with those <4 weeks (p = 0.0331). Conclusions: In order to reduce the relapse of CM and increase the survival possibility of these patients, we can promote the importance of ART before CM occurs, emphasize timely consultation when any CM-associated clinical symptoms occurs, and individualized the timing of ART initiation according to indicators which can reflect the severity of CM.